Iatrogenic exacerbation of pulmonary arteriovenous malformation in a patient with benign metastasizing leiomyoma. Issue 1 (11th December 2013) - Cadieux‐Simard, Marie‐Lie; Hennessey, Hooman; Small, David; Daskalopoulou, Stella S.; Camlioglu, Errol
Abstract We present a case of a middle‐aged woman with known benign metastasizing leiomyoma presenting with pleural effusion. After ultrasound‐guided drainage of the largest cyst was performed, the patient became hypoxemic. Chest computerized tomography (CT) showed a large tortuous vessel adjacent to the biggest cyst that had been drained. A 10‐fold increase in the diameter of this vessel was noted when compared to CT scan performed 24 h before the procedure. A 20% right‐to‐left shunt was observed on nuclear medicine shunt study. To our knowledge, this is the first reported case of metastasizing leiomyoma with coexistent pulmonary arteriovenous malformation.